The sustainability of the world’s soils - Hauser, S.; Norgrove, L. (2016)
Agriculture and food production are predominantly soil-based, with only marginal portions based on hydroponics or the use of only biomass as a substrate. In this chapter, the factors aff ecting sustainable soil use will be elaborated. This is defi ned as factors that: • maintain or improve soil biological, chemical, and physical properties; • maintain an input:output (harvest) ratio greater than one for all macronutrients; • use nutrient inputs, preferably but not exclusively from renewable rather than nonrenewable sources that seek to complement natural nutrient cycling; and • permit the system to recover from the disturbances caused by cultivation and harvest (adapted after Schaller 1993). To address and apply these themes, the attention of this chapter rests predominately on the situation in sub-Saharan Africa. There are good reasons for this geographical focus. In the twentieth century, the green revolution in Asia demonstrated that dramatic yield increases are possible in the poorer tropical regions, achieved by combining fertilizer inputs, better agronomy, improved pest management, soil water management and crop varieties (Huang et al. 2002). These, coupled with development of rural infrastructure, have sustained input supply lines and marketing and value chains. However, sub-Saharan Africa has neither experienced a green revolution nor has it the rural infrastructure or NARES to support agriculture to even keep pace with the food demands of the growing population.